Pre-weaning socialisation with non-littermates in piglets: reduced weaning stress when regrouped with unfamiliar piglets post-weaning? - Du, Dongyue; Toribio, Jenny-Ann (Veterinary Evidence, 2023)
PICO question In piglets in indoor housing systems does pre-weaning socialisation with non-littermates compared to no pre-weaning socialisation with non-littermates result in lower weaning stress when regrouped with unfamiliar piglets post-weaning? Clinical bottom line Category of research question Treatment. The number and type of study designs reviewed Nine papers were critically reviewed. All of them were controlled trials, of which two were randomised control trials. Strength of evidence Moderate. Outcomes reported In terms of behavioural indicators of weaning stress, piglets socialised with non-littermates during lactation showed less aggressive behaviours (in the six papers that investigated aggression) and fewer skin lesions (in the six out of seven papers that investigated skin lesions) than non-socialised piglets when regrouped with unfamiliar piglets post-weaning. One of two papers showed that the cortisol level of socialised piglets had a smaller increase from pre-weaning to post-weaning level than non-socialised piglets. Four out of five papers that investigated average daily weight gain (ADG) found that the difference between socialised and non-socialised piglets in ADG was insignificant. Conclusion Based on behavioural indicators, there was strong evidence suggesting that pre-weaning socialisation with non-littermates could reduce aggression and skin lesions when regrouped with unfamiliar piglets post-weaning. However, due to the weak evidence for the physiological indicator and growth performance, the effect of pre-weaning socialisation on weaning stress was inconclusive. How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.